Cancer patient disclosure and patient-doctor communication of complementary and alternative medicine use: A systematic review - Davis, E.; Oh, B.; Butow, P.; Mullan, Barbara; Clarke, S. (2014)
Objective: To explore the nondisclosure of complementary and alternative medicine (CAM) use among cancer patients, including reasons for and outcomes from nondisclosure of CAM use, within the context of patient- doctor communication. Method: A systematic review was conducted exploring investigations surrounding the communication of CAM use for patients with cancer published until August 2011. Results: A total of 21 studies were located, which reported a prevalence of CAM use among patients with cancer ranging between 11% and 95%; of these patients, 20% to 77% did not disclose their CAM use. The main reasons for nondisclosure were the doctor’s lack of inquiry; patient’s anticipation of the doctor’s disapproval, disinterest, or inability to help; and patient’s perception that disclosure of CAM use is irrelevant to their conventional care. There is some evidence to suggest that patient-doctor communication about the use of CAM was associated with an enhanced patient-doctor relationship and higher patient satisfaction. Conclusions: Although the use of CAM by patients with cancer is high, patients frequently fail to disclose its use to their health professionals for reasons emanating from both sides of the dyadic patient-doctor relationship. Because a substantial proportion of patients with cancer may use CAM and there is potential for herb- or vitamin-drug interactions, further research in patient-doctor communication about CAM is necessary to maintain patient safety and wellbeing. The development of effective interventions to improve the disclosure of CAM use should be an integral part of this future research.